The Power of the Network: Teach For America's Impact on the Deregulation of Teacher Education. Issue 3 (May 2018) - Kretchmar, Kerry; Sondel, Beth; Ferrare, Joseph J.
In this article, we illustrate the relationships between Teach For America (TFA) and the deregulation of university-based teacher education programs. We use policy network analysis to create a visual representation of TFA's connections to individuals, organizations, and private corporations who are working to shift the way teachers are prepared. In doing this, we identify human capital dependents, jurisdictional challengers, and legislative supporters who are working independently and collectively to shift our national focus from teacher education to teacher training for those teachers serving students in marginalized communities.